2021
DOI: 10.3390/app11125545
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Effect of CNTs on Early Age Hydration and Autogenous Shrinkage of Cement Composite

Abstract: In this study, the effect of carbon nanotubes (CNTs) on the physical properties of cement composites was investigated. The mechanism of the change of autogenous shrinkage of CNTs-reinforced cement composites was also examined. In the experiments, ordinary Portland cement (OPC) and fly ash (FA) were used as binders, and 0.0, 0.1, 0.3, and 0.5% multi-walled CNTs (MWCNTs) were added to fabricate pastes. When the hydration heat was measured through isothermal calorimetry, it was found that CNTs accelerated the ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…The experiment performed by Park and Choi [21] shows that the setting time of a cement composite with CNTs reduced proportionally to the amount of carbon nanotubes added by 2.4% and 3.0% for initial and final setting times, respectively. Therefore, it was concluded that CNTs accelerate the hydration process in the early stages by reducing its induction period; however, the influence in later hydration stages was not significant between different CNT amounts.…”
Section: Introductionmentioning
confidence: 99%
“…The experiment performed by Park and Choi [21] shows that the setting time of a cement composite with CNTs reduced proportionally to the amount of carbon nanotubes added by 2.4% and 3.0% for initial and final setting times, respectively. Therefore, it was concluded that CNTs accelerate the hydration process in the early stages by reducing its induction period; however, the influence in later hydration stages was not significant between different CNT amounts.…”
Section: Introductionmentioning
confidence: 99%
“…Research on utilizing CNT as a construction material continues, capitalizing on its beneficial properties [3]. CNTs can act as a filler, effectively bridging the gaps among numerous pores formed during cement hydration [4,5]. In addition, owing to their substantial specific surface area, CNTs actively accelerate cement hydration, thereby contributing to the overall enhancement of the mechanical properties of cement [6].…”
Section: Introductionmentioning
confidence: 99%